Deaf communication - García Benavides, Irene (2003)
Describing the mechanism of how deaf people have built their own language: the·Sign Language wich is natural for them, is not an easy task. Both oral and sign languages are acquired by different modalities and there are different rules operating in them. Even when both modalities have their own grammar, the linguistic universals take place in them.